2019
DOI: 10.1029/2018jb016083
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Loss and Aquifer System Compaction in San Joaquin Valley During 2012–2015 Drought

Abstract: California's millennium drought of 2012–2015 severely impacted the Central Valley aquifer system and caused permanent loss of groundwater and aquifer storage capacity. To quantify these impacts within the southern San Joaquin Valley, we analyze various complementary measurements, including gravity changes from Gravity Recovery and Climate Experiment (GRACE) satellites; vertical land motion from Global Positioning System, interferometric synthetic aperture radar, and extensometer; and groundwater level records.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 52 publications
9
58
4
Order By: Relevance
“…Excess irrigation water can also flow down through perforated groundwater well casings, which increase the vertical hydraulic conductivity between the shallow unconfined and deeper confined and semi‐confined aquifers and aid in aquifer recharge during this time (Faunt, ). It is also important to note that the largest seasonal amplitudes occur where we see peak recharge in the spring versus in the winter, showing that the largest seasonal recharge and discharge rates are dominantly controlled by agricultural activity (Ojha et al, ; Shirzaei et al, ).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Excess irrigation water can also flow down through perforated groundwater well casings, which increase the vertical hydraulic conductivity between the shallow unconfined and deeper confined and semi‐confined aquifers and aid in aquifer recharge during this time (Faunt, ). It is also important to note that the largest seasonal amplitudes occur where we see peak recharge in the spring versus in the winter, showing that the largest seasonal recharge and discharge rates are dominantly controlled by agricultural activity (Ojha et al, ; Shirzaei et al, ).…”
Section: Methodsmentioning
confidence: 91%
“…The primary disadvantage with these load change measurements is their coarse spatial resolution (~200–300 km). Spaceborne InSAR has also been proven useful in measuring compaction due to the removal of fluid (Galloway et al, ; Miller et al, ; Ojha et al, ) and, thus, can be used to estimate groundwater volume loss (Ojha et al, ). Here we use published groundwater volume loss estimates from VLM (Ojha et al, ) found using a combination of InSAR line of sight (LOS) displacements and horizontal displacements from Plate Boundary Observatory network GPS stations to evaluate the effect groundwater loss has on vertical elastic deformation outside of the Valley and changes to the magnitude of stress along faults in California.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Northeast United States, Collins (20) found minimal evidence for shifts in the timing of annual peak flows, but Hodgkins and Dudley (32) showed that the centroid of winterspring streamflow has shifted at 32 to 64% of snowmelt-affected sites in the eastern North America. In the western United States, drought has and is projected to limit snowpack generation and groundwater recharge (33)(34)(35), a pattern reflected in increased frequency of extreme low flows in the Pacific Coast and Pacific Northwest hydro-regions during summer and fall ( fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…As long as pre‐consolidation stress is not exceeded, though, the deformation is recoverable (Galloway & Burbey, 2011). It has been shown that pumping in the San Joaquin Valley during recent droughts has caused inelastic deformation, permanently reducing aquifer storage (Chaussard & Farr, 2019; Ojha et al, 2019; 2020).…”
Section: Introductionmentioning
confidence: 99%